Damage localization in bridges via the FRF interpolation method. (February 2015) - Dilena, M.; Limongelli, M.P.; Morassi, A.
Abstract: Vibration based methods are powerful tools to assess the structural behavior of a bridge. In this paper, the Interpolation Damage Detection Method is used to give an interpretation of frequency response function (FRF) measurements performed on a reinforced concrete single span bridge subject to increasing levels of concentrated damage. The sensitivity of the method is documented and discussed with respect to the amount of experimental data available and the severity of the damage. The results are encouraging. They show the ability of the method to correctly detect the damage location in the majority of the scenarios considered and to give quantitative indication of the relative severity of the damage. A comparison with the results obtained by the Modal Curvature Method is also presented. Highlights: We present a method for damage localization in bridges by frequency response data. An index which determines the loss of spatial regularity of FRFs is introduced. The method is tested on a real RC bridge subject to increasing levels of damage. The sensitivity of the method is fully documented and discussed. A comparison with the Modal Curvature Method is also presented.